Digital Cultural Transformation And Dynamics Of Islamic Religious Education: A Sociological Study Of The Relationship Between School Communities And Religious Values - Diah Feriana; Asep Mulyana; Rosidi Rido; Nurhabibi (Jurnal At-Tarbiyat: Jurnal Pendidikan Islam, 2025)
The transformation of digital culture has influenced traditional methods of delivering and internalizing the values of Islamic Religious Education (PAI) in schools. This change presents both challenges and opportunities in shaping students' spiritual understanding amidst the flood of digital information. This article aims to analyze the dynamics of integrating PAI values within the digital culture in school environments using a sociological approach. The research method employed is a qualitative-descriptive study based on a literature review, focusing on the analysis of literature related to the interaction between students, teachers, and the digital environment in religious education. The main findings show that synergy between teachers, families, and school communities is crucial in shaping a value ecosystem that adapts to digital developments. Digital spirituality can be strengthened if supported by solid religious literacy, value-based educational policies, and a reflective school culture. This article recommends integrating religious-digital literacy, enhancing PAI teacher competence, and designing contextual curricula to address the challenges of the digital era. This study contributes by offering strategies to optimize religious education in the digital world, and opens the door for further research on the influence of technology on religious education.